Resin composition, cured product, composite molded article, semiconductor device
Patent Information
- Application Number
- KR1020227013145
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-30
- Filing Date
- 2020-10-30
- Publication Date
- 2026-10-21
- Estimated Expiration
- 2040-10-30
Smart Images

Figure 112022042050492-PCT00001
Abstract
Description
Technology Field
[0001] The present invention relates to a resin composition, a cured product, a composite molded body, and a semiconductor device.
[0002] The present application claims priority based on Japanese patent application No. 2019-197273 filed in Japan on October 30, 2019, and incorporates the contents thereof herein by reference. Background Technology
[0003] Power semiconductor devices are used in various fields such as railways, automobiles, and general consumer electronics. Recently, in order to achieve further miniaturization, lower costs, and higher efficiency, there has been a transition from conventional power semiconductors using Si to power semiconductors using SiC, AlN, GaN, etc.
[0004] Power semiconductor devices are generally used as power semiconductor modules in which multiple semiconductor devices are placed on a common heatsink and packaged.
[0005] While various challenges have been pointed out regarding the practical application of such power semiconductor devices, one of them is the issue of heat dissipation generated by the devices. Generally, since high output and high density are enabled by operating power semiconductor devices at high temperatures, insufficient heat dissipation affects the reliability of the devices. For example, there are concerns that heat generated during device switching may degrade reliability.
[0006] Particularly in the recent electrical and electronic fields, as integrated circuits are becoming increasingly dense, dissipating the heat generated by this increased density is an urgent challenge.
[0007] As a method to solve this problem, ceramic substrates with high thermal conductivity, such as alumina substrates and aluminum nitride substrates, are used as heat dissipation substrates for mounting power semiconductor devices. However, ceramic substrates have drawbacks, such as being easily damaged by impact and being difficult to miniaturize due to the difficulty of making them thin films.
[0008] Thus, a heat dissipation resin sheet is proposed using an inorganic filler-containing resin composition containing a thermosetting resin, such as a high thermal conductivity epoxy resin, and a high thermal conductivity inorganic filler (e.g., Patent Document 1). Patent Document 1 describes a heat dissipation resin sheet containing a resin and a boron nitride filler, wherein the boron nitride filler content is 30 vol% or more and 60 vol% or less, and the Tg of the resin is 60 ℃ or less. Prior art literature
[0009] Japanese Patent Publication No. 2017-36415 The problem to be solved
[0010] However, in the case of a heat dissipation resin sheet using a conventional inorganic filler-containing resin composition, when applied to a power semiconductor device, the following problems (1) to (3) exist.
[0011] (1) When mounting a heat dissipation resin sheet on a power semiconductor device, a molding pressurization process is performed by applying pressure to the resin composition to adhere it to the metal and form a cured product. However, if the resin composition is stored after being manufactured and the molding pressurization process is performed after the storage period has elapsed, the curing reaction of the thermosetting resin in the resin composition progresses as the storage period increases, and there are cases where the original performance cannot be achieved during the molding process. For example, if the curing reaction of the thermosetting resin proceeds excessively, the adhesion of the heat dissipation resin sheet to the metal decreases.
[0012] (2) In addition, as a method to improve the thermal conductivity in the thickness direction of the heat dissipation resin sheet, pressure is applied to the resin composition during the molding pressurization process to make the inorganic fillers in the resin composition adhere to each other. However, if the curing reaction of the thermosetting resin proceeds excessively during storage of the resin composition, it becomes difficult for the inorganic fillers to adhere to each other even when pressure is applied during the molding pressurization process. As a result, it becomes difficult to sufficiently improve the thermal conductivity of the heat dissipation resin sheet.
[0013] To exhibit high thermal conductivity, for example, agglomerated inorganic fillers that are easily deformed by a molding pressurization process may be used. However, if the curing reaction of the thermosetting resin proceeds excessively during storage of the resin composition, the deformation of the agglomerated inorganic fillers is also inhibited, and consequently, the effect of improving thermal conductivity through enhanced adhesion between the inorganic fillers is also inhibited.
[0014] (3) In addition, as a method to improve the insulation and adhesion to metal of the heat dissipation resin sheet, pressure is applied to the resin composition during the molding pressurization process to remove voids within the resin composition and at the interface between the resin composition and the metal. However, if the curing reaction of the thermosetting resin proceeds excessively during storage of the resin composition, it becomes difficult to remove voids during the molding pressurization process. If the removal of voids is insufficient, the cured material and the metal may delaminate at the interface when heated by a reflow furnace during the manufacturing process of the power semiconductor module.
[0015] The present invention provides a resin composition having excellent thermal conductivity and adhesion to metal, thereby yielding a cured product that is difficult to peel off at the interface when combined with a metal; a resin cured product having excellent thermal conductivity and adhesion to metal, thereby making it difficult to peel off at the interface when combined with a metal; a composite molded article having excellent thermal conductivity and adhesion between the resin cured product and the metal, thereby making it difficult to peel off at the interface; and a semiconductor device having excellent heat dissipation performance and adhesion between the resin cured product and the metal, thereby making it difficult to peel off at the interface. means of solving the problem
[0016] [1] A resin composition comprising an inorganic filler, a thermosetting resin, and a thermosetting catalyst, wherein the inorganic filler comprises an aggregated inorganic filler, the thermosetting resin comprises an epoxy resin, and the resin composition comprises two or more types of thermosetting catalysts having a melting point of 100°C or higher.
[0017] [2] A resin composition of [1] having at least one type of thermosetting catalyst having a structure derived from imidazole.
[0018] [3] A resin composition of which the thermosetting catalyst having a structure derived from imidazole additionally has a structure derived from triazine in one molecule [2].
[0019] [4] A resin composition of any one of [1] to [3], wherein two or more of the above thermosetting catalysts have a structure derived from imidazole.
[0020] [5] A resin composition of any one of [1] to [4], wherein at least one of the thermosetting catalysts has a melting point of 200°C or higher.
[0021] [6] A resin composition of any one of [1] to [5] wherein the resin composition optionally additionally contains a solvent, and the content of the thermosetting catalyst is 0.1 to 10 mass% with respect to 100 mass% of the resin composition excluding the inorganic filler and the optionally included solvent.
[0022] [7] A resin composition of any one of [1] to [6], wherein the solubility of the thermosetting catalyst for N,N-dimethylformamide at 25°C is 10 mass% or less.
[0023] [8] A resin composition of any of [1] to [7] in which the above-mentioned agglomerated inorganic filler comprises boron nitride agglomerated particles.
[0024] [9] A resin composition of any of [1] to [8] additionally containing alumina.
[0025]
[10] A resin composition of any of [1] to [9] in which the above-mentioned agglomerated inorganic filler is a boron nitride agglomerated particle having a card house structure.
[0026]
[11] A resin composition of any of [1] to
[10] , the main component of the resin composition is epoxy resin.
[0027]
[12] A resin cured product using a resin composition of any of [1] ~
[11] .
[0028]
[13]
[12] A composite molded body having a resin cured product and a metal.
[0029]
[14]
[13] A semiconductor device having a composite molded body. Effects of the invention
[0030] According to the resin composition of the present invention, a cured product is obtained that is difficult to peel off at the interface when combined with a metal, as it has excellent thermal conductivity and adhesion to metal.
[0031] The resin cured product of the present invention has excellent thermal conductivity and adhesion to metal, making it difficult to delaminate at the interface when combined with metal.
[0032] The composite molded article of the present invention has excellent thermal conductivity and adhesion between the resin cured product and the metal, making it difficult to delaminate at the interface.
[0033] The semiconductor device of the present invention has excellent heat dissipation performance and adhesion between the resin cured material and the metal, making it difficult to peel off the interface. Specific details for implementing the invention
[0034] Embodiments of the present invention are described in detail below, but the present invention is not limited to the following embodiments and can be implemented with various modifications within the scope of its gist.
[0035] <Resin Composition>
[0036] The resin composition of the present invention comprises an agglomerated inorganic filler, a thermosetting resin, and a thermosetting catalyst. The resin composition of the present invention is a composition in a state prior to curing. For example, compositions in a state prior to curing, such as a slurry-type resin composition provided to the coating process described later, a sheet that has undergone a coating process, and a sheet that has undergone processes such as coating and drying, are all treated as resin compositions.
[0037] Meanwhile, a resin cured product using the resin composition of the present invention is to have an exothermic peak of 10 J / g or less when heated from 40 ℃ to 250 ℃ at a rate of 10 ℃ / min using DSC (differential scanning calorimetry).
[0038] In the resin composition of the present invention, the thermosetting resin comprises an epoxy resin, and the thermosetting catalyst comprises two or more types of thermosetting catalysts having a melting point of 100°C or higher. Accordingly, the reaction rate of the thermosetting resin can be reduced, thereby suppressing the excessive progress of the curing reaction.
[0039] Here, it is also conceivable to reduce the amount of curing catalyst to lower the reaction rate and inhibit the progress of the curing reaction. However, if the amount of curing catalyst is reduced, the curing reaction of the thermosetting resin may stop midway or proceed insufficiently. As a result, the elastic modulus of the cured product decreases, and properties such as thermal conductivity, cured product strength, dielectric properties, and heat resistance are degraded.
[0040] Therefore, in the present invention, by combining two or more different thermosetting catalysts having a melting point of 100°C or higher, the reaction rate of the thermosetting resin during storage can be reduced, and the curing reaction can be sufficiently carried out when curing in a molding pressurization process, etc. Such a resin composition can be preferably used as a material for a heat dissipation sheet for a power semiconductor device, and a highly reliable power semiconductor module can be realized.
[0041] (Weapon Filler)
[0042] The resin composition of the present invention comprises an inorganic filler. The inorganic filler comprises an agglomerated inorganic filler. In addition to the agglomerated inorganic filler, the inorganic filler may further comprise a non-agglomerated inorganic filler. However, in order to improve the thermal conductivity of the resin cured product of the present invention and to control the coefficient of linear expansion, it is preferable to increase the proportion of the agglomerated inorganic filler among the inorganic fillers.
[0043] Since the resin composition of the present invention includes aggregated inorganic fillers among the inorganic fillers, the aggregated inorganic fillers are deformed by coming into contact with each other during the molding pressurization process, making surface contact easy. As a result, more heat conduction paths are formed, and the thermal conductivity of the cured product tends to increase. The aggregation form of the aggregated inorganic fillers can be confirmed by scanning electron microscopy (SEM).
[0044] The resin composition of the present invention may use, in addition to the inorganic filler, a non-aggregating inorganic filler and an organic filler.
[0045] As for the cohesive inorganic filler, an electrically insulating inorganic compound is preferred. For example, a filler composed of at least one particle selected from the group consisting of metal carbides, metal oxides, and metal nitrides may be used.
[0046] Examples of metal carbides include silicon carbide, titanium carbide, and tungsten carbide.
[0047] Examples of metal oxides include magnesium oxide, aluminum oxide, silicon oxide, calcium oxide, zinc oxide, yttrium oxide, zirconium oxide, cerium oxide, ytterbium oxide, and sialon (ceramics composed of silicon, aluminum, oxygen, and nitrogen).
[0048] Examples of metal nitrides include boron nitride, aluminum nitride, silicon nitride, etc.
[0049] Among these, metal oxides and metal nitrides are preferred because the resin cured material has excellent electrical insulation properties.
[0050] Given that power semiconductors require insulation, it is desirable for the condensed inorganic filler to be composed of an inorganic compound with excellent insulation properties. Specifically, a compound with a volume resistivity of 1 × 10⁻⁶ 13 An inorganic compound having an Ω·cm or higher is preferred, and a volume resistivity of 1 × 10⁻⁶ 14 Inorganic compounds with a Ω·cm or larger value are more preferable.
[0051] Inorganic compounds with excellent insulating properties include, for example, alumina (Al2O3, volume resistivity: 1 × 10⁻⁶). 14 Ω·cm), aluminum nitride (AlN, volume resistivity: 1 × 10⁻⁶ 14 Ω·cm), boron nitride (BN, volume resistivity: 1 × 10⁻⁶ 14 Ω·cm), silicon nitride (Si3N4, volume resistivity 1 × 10⁻⁶ 14 Ω·cm), silica (SiO2, volume resistivity 1 × 10⁻⁶ 14 Examples include Ω·cm).
[0052] Among these, alumina, aluminum nitride, boron nitride, and silica are preferred, and alumina and boron nitride are more preferred.
[0053] The cohesive inorganic filler may be surface-treated with a surface treatment agent. Known surface treatment agents may be used.
[0054] The cohesive inorganic filler may be used as a single type, or two or more types may be mixed in any combination and ratio.
[0055] The method and degree of aggregation of the aggregated inorganic filler are not particularly limited. However, it is preferable to use the following boron nitride aggregated particles as the aggregated inorganic filler. Additionally, fillers of different shapes and types may be used in combination with the boron nitride aggregated particles.
[0056] [Boron Nitride Aggregated Particles]
[0057] Boron nitride has high thermal conductivity but is flaky; it conducts heat in the planar direction but has high thermal resistance in the direction perpendicular to the plane. To improve handling, it is desirable to use aggregated particles in which the flaky particles are gathered and aggregated into a spherical shape.
[0058] For boron nitride aggregate particles, it is desirable to have a card house structure.
[0059] The “card house structure” is described, for example, in Ceramics 43 No. 2 (published by the Japan Ceramics Association in 2008), and is a structure in which plate-like particles are not oriented but are complexly stacked.
[0060] More specifically, the boron nitride aggregated particle having a card house structure is an aggregate of boron nitride primary particles having a structure in which the planar portion and cross-sectional portion of the primary particles come into contact to form, for example, a T-shaped aggregate.
[0061] As for the boron nitride aggregate particles used in the present invention, boron nitride aggregate particles having the card house structure are particularly preferred, and by using boron nitride aggregate particles having the card house structure, the thermal conductivity can be further increased.
[0062] The new Mohs hardness of the boron nitride aggregate particles is not particularly limited, but is preferably 5 or less. If the new Mohs hardness is 5 or less, contact between particles dispersed in the resin composition is easy to make surface contact, and heat conduction paths between particles are formed, which tends to improve the heat conductivity of the resin cured product. The lower limit of the new Mohs hardness is not particularly limited, but is, for example, 1 or more.
[0063] The volume average particle size of the boron nitride aggregate particles is not particularly limited, but it is preferably 10 μm or more, and more preferably 15 μm or more. If the volume average particle size is greater than the lower limit above, the number of particles in the resin composition and the cured product using the resin composition becomes relatively small, so the inter-particle interface becomes smaller, which reduces thermal resistance and may result in the composite resin sheet having high thermal conductivity.
[0064] In addition, the volume average particle size of the boron nitride aggregate particles is preferably 100 μm or less, and more preferably 90 μm or less. If the volume average particle size is below the upper limit, surface smoothness of the cured product using the resin composition tends to be obtained.
[0065] Here, the volume-average particle size of the boron nitride aggregated particles refers to the particle size at which the cumulative volume reaches 50% when a cumulative curve is drawn with the volume of the powder provided for measurement set to 100%. Measurement methods include a wet measurement method, in which the aggregated particles are dispersed in a pure medium containing sodium hexametaphosphate as a dispersion stabilizer, using a laser diffraction / scattering particle size distribution measuring device, and a dry measurement method, in which the "Morphologi" manufactured by Malvern is used. The same applies to the spherical filler described below.
[0066] [Content of cohesive inorganic filler]
[0067] The content of the aggregated inorganic filler in the resin composition of the present invention is preferably 20 mass% or more with respect to 100 mass% of the resin composition, more preferably 30 mass% or more, more preferably 40 mass% or more, and particularly preferably 50 mass% or more. Furthermore, the content of the aggregated inorganic filler in the resin composition of the present invention is preferably 99 mass% or less with respect to 100 mass% of the resin composition, more preferably 90 mass% or less, and particularly preferably 80 mass% or less.
[0068] In addition, the combination of upper and lower limits of the content of the aggregated inorganic filler is not particularly limited, but 20 mass% or more and 99 mass% or less is preferred, 30 mass% or more and 99 mass% or less is more preferred, 40 mass% or more and 90 mass% or less is more preferred, and 50 mass% or more and 80 mass% or less is particularly preferred.
[0069] If the content of the aggregated inorganic filler is above the above lower limit, there is a tendency to sufficiently obtain the effect of improving thermal conductivity and controlling the coefficient of linear expansion due to the inclusion of the aggregated inorganic filler. Furthermore, if the content of the aggregated inorganic filler is below the above upper limit, there is a tendency for the moldability of the resin cured product and the interfacial adhesion in the composite molded body to be improved.
[0070] In addition to the agglomerated inorganic filler, when other non-agglomerated inorganic fillers are used in combination, the content ratio of the agglomerated inorganic filler and other non-agglomerated inorganic filler in the resin composition is not particularly limited, but it is preferable that the mass ratio is 90:10 to 10:90, and more preferable that it is 80:20 to 20:80.
[0071] [Destructive Strength of Cohesive Weapon Fillers]
[0072] The fracture strength of the aggregated inorganic filler is not particularly limited, but is preferably 300 MPa or less, more preferably 100 MPa or less, even more preferably 50 MPa or less, even more preferably 20 MPa or less, particularly preferably 15 MPa or less, and most preferably 10 MPa or less. If the fracture strength is below the above upper limit, the aggregated structure of the aggregated inorganic filler is deformed when press-treated, making it easy for the aggregated inorganic fillers to come into surface contact with each other. Meanwhile, the lower limit of the fracture strength is not particularly limited, but for ease of handling, the fracture strength is preferably 2.5 MPa or more, more preferably 3 MPa or more, even more preferably 3.5 MPa or more, and particularly preferably 4 MPa or more.
[0073] If the fracture strength of the aggregated inorganic filler is within the above numerical range, the portion where the aggregated inorganic fillers are in contact with each other tends to deform, making surface contact easier. By maintaining the high thermal conductivity within the aggregated inorganic filler and lowering the contact thermal resistance at the interface between the aggregated inorganic filler and the interface between the metal substrate and the heat dissipation sheet described later, the overall thermal conductivity can be improved.
[0074] [Elasticity Modulus of Cohesive Inorganic Filler]
[0075] The elastic modulus of the cohesive inorganic filler is not particularly limited, but is preferably 10 MPa or higher, more preferably 20 MPa or higher, even more preferably 30 MPa or higher, particularly preferably 50 MPa or higher, and most preferably 55 MPa or higher. If the elastic modulus is above the lower limit, the cohesive inorganic filler tends to undergo plastic deformation in the direction of the press pressure, thereby suppressing the collapse of the cohesive structure. Meanwhile, the upper limit of the elastic modulus is not particularly limited, but is preferably 5 GPa or lower, more preferably 2 GPa or lower, even more preferably 1.5 GPa or lower, even more preferably 1 GPa or lower, even more preferably 500 MPa or lower, particularly preferably 300 MPa or lower, and most preferably 150 MPa or lower.
[0076] If the elastic modulus of the cohesive inorganic filler is within the above numerical range, it tends to maintain its spherical shape during press processing.
[0077] The fracture strength and elastic modulus of the cohesive inorganic filler can be measured after removing the cohesive inorganic filler by burning the resin of the heat dissipation sheet so that the cohesive inorganic filler does not deteriorate when the cohesive inorganic filler is inside the heat dissipation sheet.
[0078] [Other non-cohesive inorganic fillers]
[0079] Apart from aggregated inorganic fillers, other non-aggregated inorganic fillers may be used in combination. Examples of other non-aggregated inorganic fillers include spherical fillers in addition to those described above. Other non-aggregated fillers are not limited to spherical fillers. For example, flaky boron nitride primary particles may be used, and they are not limited to spherical fillers.
[0080] The thermal conductivity of the spherical filler is preferably 10 W / m·K or higher, more preferably 15 W / m·K or higher, and even more preferably 20 W / m·K or higher. The thermal conductivity of the spherical filler is, for example, preferably 10 to 30 W / m·K. The new Mohs hardness of the spherical filler is preferably 3.1 or higher. The new Mohs hardness of the spherical filler is, for example, preferably 5 to 10. By using such a spherical filler in combination with the aforementioned agglomerated inorganic filler, the adhesion to metal and heat dissipation properties of the resulting resin cured product can be increased.
[0081] Here, "spherical" means that it is generally recognized as spherical, for example, an average circularity of 0.4 or higher may be considered spherical, or 0.6 or higher may be considered spherical. Typically, the upper limit of the average circularity is 1. The circularity can be measured by image processing of the projected image, and can be measured, for example, using Sysmex's FPIA series.
[0082] The spherical filler is preferably at least one selected from the group consisting of alumina, synthetic magnesite, crystalline silica, aluminum nitride, silicon nitride, silicon carbide, zinc oxide, and magnesium oxide. By using these preferred spherical fillers, the heat dissipation of the resulting resin cured product can be further enhanced.
[0083] The average particle size of the spherical filler is preferably 0.5 μm or more and 40 μm or less. If the average particle size is 0.5 μm or more, the resin and filler can flow easily during heat molding, which is thought to increase the interfacial adhesion strength in the composite molded body of the present invention. In addition, if the average particle size is 40 μm or less, it becomes easier to maintain the dielectric breakdown characteristics of the resin cured product.
[0084] There are no restrictions on the shape of the inorganic filler, and it may be particulate, whisker-like, fibrous, plate-like, or aggregates thereof.
[0085] [Organic Filler]
[0086] In addition to the aggregated inorganic filler, an organic filler may be used in combination. In the present invention, the organic filler is a component that is solid at room temperature and is composed of organic components, does not contain epoxy groups, does not correspond to a thermosetting catalyst, and is composed of organic components. Examples of organic fillers include natural materials such as wood flour, cellulose that may be modified, starch, various organic pigments, thermoplastic resins, thermosetting resins, etc. Specific examples include acrylic resin particles, nylon resin particles, polyester resin particles, polystyrene resin particles, silicone resin particles, etc. One of these may be used alone, or two or more may be used in combination.
[0087] If organic fillers are included, it may be possible to impart appropriate elongation to the resin composition, relieve stress, and suppress the occurrence of cracks during temperature cycle tests.
[0088] The upper limit of the average particle size of the organic filler is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 30 μm or less. If the average particle size of the organic filler is below the above upper limit, the concern regarding a decrease in thermal conductivity can be reduced when manufacturing heat dissipation insulating sheets of various thicknesses. The particle size of the organic filler is the average particle size that can be obtained from the particle size distribution measurement results in volume average measured by a laser diffraction particle size distribution measuring device.
[0089] (Thermosetting resin)
[0090] The thermosetting resin included in the resin composition of the present invention is not particularly limited, provided that it can be cured in the presence of a curing agent and a curing catalyst to obtain a cured product.
[0091] Examples of thermosetting resins include, specifically, epoxy resin, phenolic resin, polycarbonate resin, unsaturated polyester resin, urethane resin, melamine resin, urea resin, etc. Among these, epoxy resin is preferred in terms of viscosity, heat resistance, hygroscopicity, and handling properties. Examples of epoxy resins include silicon compounds containing epoxy groups, aliphatic epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, novolak type epoxy resin, alicyclic epoxy resin, glycidyl ester type epoxy resin, polyfunctional epoxy resin, polymeric epoxy resin, etc.
[0092] [Epoxy Resin]
[0093] Epoxy resin is a general term for compounds having one or more oxirane rings (epoxy groups) within a molecule. Furthermore, the oxirane rings (epoxy groups) included in the epoxy resin may be either alicyclic epoxy groups or glycidyl groups, but glycidyl groups are more preferred from the perspective of reaction rate and heat resistance.
[0094] The epoxy resin used in the present invention may be a compound containing an aromatic oxirane ring (epoxy group). Specific examples include: a bisphenol-type epoxy resin obtained by glycidylating bisphenols such as bisphenol A, bisphenol F, bisphenol AD, bisphenol S, tetramethylbisphenol A, tetramethylbisphenol F, tetramethylbisphenol AD, tetramethylbisphenol S, and tetrafluorobisphenol A; a biphenyl-type epoxy resin obtained by glycidylating divalent phenols such as dihydroxynaphthalene and 9,9-bis(4-hydroxyphenyl)fluorene; an epoxy resin obtained by glycidylating trisphenols such as 1,1,1-tris(4-hydroxyphenyl)methane; and an epoxy resin obtained by glycidylating tetrakisphenols such as 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane. Examples include novolak-type epoxy resins obtained by glycidylating novolaks such as phenol novolak, cresol novolak, bisphenol A novolak, and brominated bisphenol A novolak.
[0095] The epoxy resin included in the resin composition of the present invention is not particularly limited, but includes, for example, various bisphenol-type epoxy resins obtained by glycidylating bisphenols such as bisphenol A-type epoxy resin and bisphenol F-type epoxy resin; various biphenyl-type epoxy resins obtained by glycidylating biphenyls; epoxy resins obtained by glycidylating aromatic compounds having two hydroxyl groups such as dihydroxynaphthalene and 9,9-bis(4-hydroxyphenyl)fluorene; epoxy resins obtained by glycidylating trisphenols such as 1,1,1-tris(4-hydroxyphenyl)methane; epoxy resins obtained by glycidylating tetrakisphenols such as 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane; and novolak-type epoxy resins obtained by glycidylating novolaks such as phenol novolak, cresol novolak, bisphenol A novolak, and brominated bisphenol A novolak. At least one or two types selected from the group consisting of silicone-containing epoxy resin and silicone-containing resin are preferred.
[0096] It is more preferable that the epoxy resin used in the present invention contains a polyfunctional epoxy resin. A polyfunctional epoxy resin is an epoxy resin having three or more oxirane rings (epoxy groups) per molecule.
[0097] From the perspective of increasing the storage modulus of the resin cured product of the present invention, particularly increasing the storage modulus at high temperatures, an epoxy resin having two or more oxirane rings (epoxy groups) in the molecule is preferred, an epoxy resin having three or more oxirane rings (epoxy groups) in the molecule is more preferred, and an epoxy resin having four or more glycidyl groups in the molecule is even more preferred. The storage modulus of the resin cured product at high temperatures becomes important when the amount of heat generated, such as in power semiconductors, is high.
[0098] By having multiple oxirane rings (epoxy groups), particularly glycidyl groups, within the molecule, the crosslinking density of the cured product is improved, and the resulting resin cured product becomes stronger. Therefore, when internal stress occurs in the resin cured product during a moisture absorption reflow test, the resin cured product does not deform or break but maintains its shape, thereby suppressing the formation of voids or other pores within the resin cured product.
[0099] In addition, from the perspective of increasing the storage modulus of the resin cured product, the molecular weight of the polyfunctional epoxy resin is preferably 1,000 or less, and preferably 800 or less. Also, the lower limit of the molecular weight of the polyfunctional epoxy resin is not particularly limited, but, for example, is 100 or more.
[0100] By adding a polyfunctional epoxy resin, it is possible to introduce highly polar oxirane rings (epoxy groups) at a high density. As a result, the effects of physical interactions such as van der Waals forces and hydrogen bonding are increased, which can improve the adhesion between the metal and the resin-cured product in the composite molded article.
[0101] In addition, by adding a polyfunctional epoxy resin, it is possible to increase the storage modulus of the resin cured product after heat curing. Consequently, after the cured product of the resin composition penetrates the irregularities of the metal substrate, it exhibits a strong anchoring effect, thereby improving the adhesion between the metal and the resin cured product.
[0102] On the one hand, while the hygroscopicity of the resin composition tends to increase with the introduction of a polyfunctional epoxy resin, the increase in hygroscopicity can be suppressed by reducing the amount of hydroxyl groups during the reaction through improved reactivity of the oxirane ring (epoxy group). In addition, by preparing a resin composition by combining the aforementioned epoxy resin and the polyfunctional epoxy resin, it becomes possible to achieve both high elasticity and low hygroscopicity of the resin cured product.
[0103] As for the polyfunctional epoxy resin, specifically, an epoxy resin having three or more epoxy groups is preferred, and for example, EX321L, DLC301, DLC402 manufactured by Nagase Chemtex Co., Ltd., BATG, PETG manufactured by Showa Electric Co., Ltd., etc. can be used.
[0104] These polyfunctional epoxy resins may be used as a single type or in combination of two or more types.
[0105] [Thermosetting resin content]
[0106] The content of the thermosetting resin in the resin composition of the present invention is preferably 5 to 90 mass% with respect to 100 mass% of the resin composition excluding inorganic fillers and solvents, and more preferably 10 to 60 mass%, when the resin composition optionally contains a solvent. If the content of the thermosetting resin is above the lower limit, the moldability is improved. If the content of the thermosetting resin is below the upper limit, the content of other components can be secured, thereby increasing thermal conductivity.
[0107] In addition, when excluding the solvent, inorganic filler, and thermosetting catalyst from the resin composition of the present invention, the main component is preferably an epoxy resin. Here, the term "main component" refers to the component with the largest amount.
[0108] The proportion of epoxy resin in the resin composition excluding inorganic fillers and thermosetting catalysts is not particularly limited, but it is preferably 20 mass% or more, and preferably 45 mass% or more.
[0109] In addition, the upper limit of the ratio of epoxy resin is 100 mass%, and it may be entirely epoxy resin. By having the ratio of epoxy resin within the above range, low moisture absorption, high elastic modulus, high toughness, and easy reaction control are achieved, and there is a tendency to exhibit effects such as resistance to cyclic flow, high reliability in cycle tests, and high thermal conductivity.
[0110] The resin composition of the present invention preferably contains 5 mass% or more of the polyfunctional epoxy resin, which is the aforementioned preferred epoxy resin, in the total epoxy resin, and more preferably contains 10 mass% or more. Furthermore, the resin composition of the present invention preferably contains 50 mass% or less of the polyfunctional epoxy resin in the total epoxy resin, and more preferably contains 40 mass% or less. If the content of the polyfunctional epoxy resin is above the above lower limit, the aforementioned effects of containing the polyfunctional epoxy resin can be effectively obtained. On the other hand, if the content of the polyfunctional epoxy resin is below the above upper limit, the hygroscopicity of the cured product is suppressed, and the strength performance of the cured product is also excellent, making it possible to achieve both.
[0111] From the perspective of film-forming properties, low moisture absorption, and flexibility, it is more preferable that the epoxy resin used in the present invention contains a high molecular weight epoxy resin. Specifically, the high molecular weight epoxy resin is preferably an epoxy resin with a mass average molecular weight of 10,000 or more, more preferably an epoxy resin with a mass average molecular weight of 20,000 or more, and particularly preferably an epoxy resin with a mass average molecular weight of 30,000 or more. Furthermore, the high molecular weight epoxy resin is preferably an epoxy resin with a molecular weight of 100,000 or less, and even more preferably an epoxy resin with a molecular weight of 80,000 or less.
[0112] It is preferable that the high molecular weight epoxy resin be more hydrophobic. Specifically, it is preferable to have a weight of 5,000 g / equivalent or more, and more preferable to have a weight of 7,000 g / equivalent or more. In addition, it is preferable to have a weight of 20,000 g / equivalent or less.
[0113] Here, the mass average molecular weight of the epoxy resin is a polystyrene equivalent value measured by gel permeation chromatography. Also, the epoxy equivalent is defined as "the mass of an epoxy resin containing 1 equivalent of an epoxy group" and can be measured in accordance with JIS K 7236.
[0114] One type of such high molecular weight epoxy resin may be used, or two or more types may be used in combination. Other epoxy resins that are not high molecular weight may also be used in combination.
[0115] (Thermosetting catalyst)
[0116] The resin composition of the present invention comprises two or more thermosetting catalysts having a melting point of 100°C or higher. By using these thermosetting catalysts, the reaction rate of the thermosetting resin during storage can be reduced. Furthermore, when curing in a molding pressurization process, the curing reaction can be sufficiently carried out.
[0117] When a resin composition contains only a single type of thermosetting catalyst, it is difficult to obtain the effects of the present invention. For example, if the amount of a single thermosetting catalyst is excessively increased to increase the reaction rate, the storage stability of the resin composition may deteriorate. Furthermore, as the reaction rate increases, the deformation and contact of the inorganic filler during pressurization are inhibited, so the resin cured product tends not to have high thermal conductivity. On the other hand, if the amount of a single thermosetting catalyst is excessively reduced, the curing rate slows down, and as a result, the resin composition becomes defective, resulting in a resin cured product with low elastic modulus and high moisture absorption. Consequently, during the moisture absorption reflow test, the interface between the metal and the resin cured product tends to delaminate, or voids within the resin cured product expand, leading to a decrease in insulation performance. Therefore, it is important to use two or more types of thermosetting catalysts with a melting point of 100°C or higher in combination to control the curing rate during pressurization and prevent the final cured product from becoming defective.
[0118] The thermosetting catalyst is not particularly limited, and is not particularly limited as long as two or more thermosetting catalysts having a melting point of 100°C or higher are used. In addition, it is preferable that at least one type has a melting point of 200°C or higher, and it is more preferable that two or more types have a melting point of 200°C or higher. Since one or more types have a melting point of 200°C or higher, the reaction rate of the thermosetting resin during storage can be further reduced, which is more preferable from the perspective of storage stability.
[0119] The difference (absolute value) in the melting points of two or more types of thermosetting catalysts is not particularly limited, but it is preferable that it be 100°C or lower, and more preferable that it be 80°C or lower. Also, it is preferable that it be 5°C or higher. By being within these ranges, the reaction rate of the thermosetting resin during storage can be reduced, and in cases where it is cured in a molding pressurization process, the curing reaction tends to proceed sufficiently.
[0120] Examples of thermosetting catalysts with a melting point of 100°C or higher include imidazole compounds; chain-type or cyclic tertiary amines; organophosphorus compounds; diazabicycloalkenes such as quaternary phosphonium salts and organic acid salts. In addition, organometallic compounds, quaternary ammonium salts, metal halides, etc. may be used. Examples of the organometallic compounds include zinc octylate, tin octylate, aluminum acetylacetone complexes, etc.
[0121] In order to enhance the effect of improving the adhesion between the resin cured product of the present invention and the metal, it is preferable that at least one type of thermosetting catalyst has a structure derived from imidazole, and furthermore, it is more preferable that two or more types have a structure derived from imidazole.
[0122] In addition, to improve adhesion and suppress delamination after reflow, it is desirable for the thermosetting catalyst to additionally have a structure derived from triazine. In particular, from the perspective of adhesion, it is desirable that at least one type of thermosetting catalyst having a structure derived from imidazole further has a structure derived from triazine within one molecule. Two or more types of thermosetting catalysts may have a structure derived from imidazole and a structure derived from triazine within one molecule. With these structures, the structure derived from triazine interacts with the metal through hydrogen bonding, etc., to improve adhesion, and at the same time, since the polymerization of the epoxy is initiated from the structure derived from imidazole within the same molecule, the adhesion between the resin cured product and the metal tends to be further improved.
[0123] Preferred imidazole-based compounds and triazine-based compounds having a melting point of 100 °C or higher include, for example, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(17')]-ethyl-s-triazine, 2-phenyl-4,5-dihydroxymethylimidazole, 2-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, and 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine. Examples include 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, etc.
[0124] Among these, structures derived from imidazole and structures derived from triazines are particularly preferred, and structures derived from triazines are particularly preferred, and among triazines, structures derived from 1,3,5-triazines are particularly preferred. In addition, it is acceptable for a structure to have multiple of the exemplified structural parts. Since these structures have high compatibility with thermosetting resins and a high reaction activation temperature, the curing speed and physical properties after curing can be easily adjusted. Therefore, there is a tendency to realize improved storage stability of the resin composition and additional improvement in adhesive strength after heat molding.
[0125] [Content of thermosetting catalyst]
[0126] The content of the thermosetting catalyst is preferably 0.1 to 10 mass% with respect to 100 mass% of the resin composition of the present invention excluding solvents and inorganic fillers, more preferably 0.1 to 5 mass%, and even more preferably 0.5 to 4 mass%. If the content of the curing catalyst is above the lower limit, the progress of the curing reaction can be sufficiently promoted to achieve good curing. If the content of the curing catalyst is below the upper limit, the curing speed does not become excessively fast. Therefore, if the content of the thermosetting catalyst is within the above numerical range, the storage stability of the resin composition of the present invention is improved, the thermal conductivity of the cured product is enhanced, and insulation properties can be improved by efficiently removing voids within the cured product.
[0127] Here, the solvent is not an essential component in the resin composition of the present invention. That is, the resin composition of the present invention may or may not include a solvent.
[0128] When the resin composition of the present invention includes a solvent, the content of the thermosetting catalyst is expressed as a ratio (mass%) to the amount excluding the solvent and inorganic filler from the total amount of the resin composition.
[0129] In cases where the resin composition of the present invention does not contain a solvent, the content of the thermosetting catalyst is expressed as a ratio (mass%) to the amount excluding the inorganic filler from the total amount of the resin composition.
[0130] In addition, the content of a thermosetting catalyst having both sides of a structure derived from triazine in one molecule is preferably 0.01 to 5 mass% with respect to 100 mass% of the resin composition excluding inorganic fillers and solvents, more preferably 0.15 to 5 mass%, and even more preferably 0.2 to 4 mass%. By being within these ranges, adhesion to copper plates, etc. tends to be improved.
[0131] In addition, the content of a thermosetting catalyst having both a structure derived from imidazole and a structure derived from triazine in one molecule is preferably 0.1 to 5 mass%, more preferably 0.5 to 4 mass%, and even more preferably 0.7 to 3 mass% with respect to 100 mass% of the resin composition excluding inorganic fillers and solvents. If these contents are above the lower limit, the progress of the curing reaction is sufficiently promoted, and good curing can be achieved. If the content of the thermosetting catalyst having both a structure derived from imidazole and a structure derived from triazine in one molecule is below the upper limit, the curing speed does not become excessively fast, and thus the storage stability of the resin composition of the present invention is good, the thermal conductivity of the cured product is improved, and the insulation is improved by efficiently removing voids within the cured product.
[0132] The average particle size of the thermosetting catalyst is not particularly limited, but the average particle size of at least one thermosetting catalyst is preferably 15 μm or less, and more preferably 10 μm or less. In addition, the average particle size of at least one thermosetting catalyst is preferably 50 nm or more, more preferably 100 nm or more, even more preferably 500 nm or more, and even more preferably 1000 nm or more. If the average particle size is below the above upper limit, the solubility of the thermosetting catalyst in the resin component is improved, and the reaction rate tends to improve. In addition, the elastic modulus of the resin cured product can be made higher, and the glass transition temperature can be raised. Furthermore, the dispersibility of the thermosetting catalyst is improved, and storage stability tends to improve.
[0133] Meanwhile, if the average particle size is greater than or equal to the above lower limit, secondary aggregation of the thermosetting catalyst itself is suppressed, and the dispersibility of the thermosetting catalyst is improved, which tends to enhance the storage stability of the resin composition. In addition, the handling properties during the manufacture of the resin composition also tend to improve.
[0134] The average particle size of the plurality of thermosetting catalysts is not particularly limited, but the average particle size of the plurality of thermosetting catalysts may be within the above range.
[0135] The thermosetting catalyst of the present invention preferably has at least one type having a solubility of 10 mass% or less in N,N-dimethylformamide (DMF) at 25°C, and more preferably 8 mass% or less. The lower limit of the said solubility in DMF is not particularly limited, but, for example, it may be 0.01 mass% or less. In addition, it is particularly preferable that the solubility of two or more types of thermosetting catalysts in DMF is 10 mass% or less. Since DMF is a highly polar solvent, the reaction of the thermosetting catalyst is suppressed by the insolubility of the thermosetting catalyst in DMF, and the storage stability of the resin composition tends to be improved.
[0136] (Hardening agent)
[0137] The resin composition of the present invention may additionally contain a curing agent. The curing agent is not particularly limited, but, for example, a phenolic resin, an acid anhydride having an aromatic or alicyclic skeleton, a water additive of the acid anhydride, or a modified product of the acid anhydride is preferred. By using these preferred curing agents, a resin cured product with an excellent balance of heat resistance, moisture resistance, and electrical properties tends to be obtained. Only one type of curing agent may be used, or two or more types may be used in combination.
[0138] The phenolic resin used in the curing agent is not particularly limited. Specific examples of phenolic resins include phenol novolak, o-cresol novolak, p-cresol novolak, t-butylphenol novolak, dicyclopentadiene cresol, polyparavinylphenol, bisphenol A type novolak, xylylene-modified novolak, decalin-modified novolak, poly(di-o-hydroxyphenyl)methane, poly(di-m-hydroxyphenyl)methane, poly(di-p-hydroxyphenyl)methane, etc. Among these, for further improvement of the flexibility and flame retardancy of the resin composition and for improvement of the mechanical properties and heat resistance of the cured resin, a novolak-type phenolic resin having a rigid main chain backbone; or a phenolic resin having a triazine backbone is preferred. In addition, for improvement of the flexibility of the resin composition and the toughness of the cured resin, a phenolic resin having an allyl group is preferred.
[0139] Commercially available products of the above phenolic resin include MEH-8005, MEH-8000H, and NEH-8015 manufactured by Meiwa Chemical Co.; YLH903 manufactured by Mitsubishi Chemical Co.; LA-7052, LA-7054, LA-7751, LA-1356, and LA-3018-50P manufactured by Dainippon Ink Co.; and PSM6200, PS6313, and PS6492 manufactured by Gunei Chemical Industry Co., Ltd.
[0140] Acid anhydrides having an aromatic backbone used as curing agents, aqueous additives of said acid anhydrides, and modified products of said acid anhydrides are not particularly limited. Specific examples include SMA resin EF30 and SMA resin EF60 manufactured by Satomer Japan; ODPA-M and PEPA manufactured by Manac; Rikagit MTA-10, Rikagit TMTA, Rikagit TMEG-200, Rikagit TMEG-500, Rikagit TMEG-S, Rikagit TH, Rikagit MH-700, Rikagit MT-500, Rikagit DSDA, and Rikagit TDA-100 manufactured by Shin Nippon Ricca; and EPICLON B4400 and EPICLON B570 manufactured by Dainippon Ink Chemical Co., Ltd.
[0141] Preferably, an acid anhydride having a cyclic skeleton, a water additive of the acid anhydride, and a modified product of the acid anhydride have a polycyclic skeleton, a water additive of the acid anhydride, a modified product of the acid anhydride, an acid anhydride having a cyclic skeleton obtained by an addition reaction of a terpene compound and maleic anhydride, a water additive of the acid anhydride, and a modified product of the acid anhydride have a cyclic skeleton. Specific examples include Rikajit HNA and Rikajit HNA-100 manufactured by Shin Nippon Rika Co., Ltd.; and Epicure YH306 and Epicure YH309 manufactured by Mitsubishi Chemical Co., Ltd.
[0142] It is preferable that the curing agent be included in an amount of 0 to 70 mass% with respect to 100 mass% of the resin composition excluding inorganic fillers and solvents, and particularly preferable that it be included in an amount of 0 to 55 mass%. If the content of the curing agent is above the lower limit, sufficient curing performance can be obtained. If the content of the curing agent is below the upper limit, the curing reaction proceeds effectively, the crosslinking density is improved, and the strength can be increased, thereby further improving film formation properties.
[0143] When the thermosetting resin is an epoxy resin, the content of the reactive group of the curing agent is not particularly limited, but with respect to the amount of epoxy groups in the thermosetting resin, it may be 0 equivalents, preferably 0.05 equivalents or more, more preferably 0.1 equivalents or more, even more preferably 0.15 equivalents or more, and particularly preferably 0.2 equivalents or more. Also, with respect to the amount of epoxy groups in the thermosetting resin, it is preferably 2 equivalents or less, more preferably 0.9 equivalents or less, even more preferably 0.6 equivalents or less, and particularly preferably 0.4 equivalents or less.
[0144] Regarding the amount of epoxy groups in the thermosetting resin, if the content of the reactive groups in the curing agent is above the above lower limit, the reduction in the curing speed is suppressed, making it difficult for epoxy groups to remain, and thus tends to result in improved strength and suppressed hygroscopicity of the cured resin. On the other hand, if it is below the above upper limit, the elastic modulus of the cured resin tends to increase.
[0145] (Other ingredients)
[0146] The resin composition of the present invention may additionally contain other components other than inorganic fillers, thermosetting resins, thermosetting catalysts, and curing agents, to the extent that it does not impede the effects of the present invention.
[0147] Other components may include surface treatment agents such as silane coupling agents that improve the interfacial adhesion strength between inorganic fillers used in some cases when manufacturing a resin cured product using a resin composition; insulating carbon components such as reducing agents; viscosity modifiers; dispersants; thixotropic agents; flame retardants; coloring agents; organic solvents; and thermoplastic resins.
[0148] Among these, if the resin composition additionally contains a dispersant, it becomes possible to form a uniform resin cured product, which may improve the thermal conductivity and dielectric breakdown characteristics of the resulting resin cured product. Additionally, if the resin composition additionally contains a thermoplastic resin, it may impart appropriate elongation to the resin composition and relieve stress, thereby suppressing the occurrence of cracks during temperature cycle testing.
[0149] It is preferable that the dispersant has a functional group containing a hydrogen atom having hydrogen bonding capabilities. By having a functional group containing a hydrogen atom having hydrogen bonding capabilities, the thermal conductivity and dielectric breakdown characteristics of the resin cured product can be further enhanced. Examples of the functional groups containing a hydrogen atom having hydrogen bonding capabilities include a carboxyl group (pKa = 4), a phosphate group (pKa = 7), a phenol group (pKa = 10), etc.
[0150] The pKa of the functional group containing a hydrogen atom having hydrogen bonding ability is preferably 2 to 10, and more preferably 3 to 9. If the pKa is 2 or higher, the acidity of the dispersant becomes within a suitable range, and the reaction of the epoxy resin in the thermosetting resin component may be easily suppressed. Therefore, when the molded article in an uncured state is stored, storage stability tends to be improved. By having a pKa of 10 or lower, it can sufficiently perform its function as a dispersant and tends to sufficiently increase the thermal conductivity and dielectric breakdown characteristics of the resin-cured article.
[0151] As functional groups containing hydrogen atoms capable of hydrogen bonding, carboxyl groups and phosphate groups are preferred. In this case, the thermal conductivity and dielectric breakdown characteristics of the resin cured product can be further enhanced.
[0152] Examples of dispersants include, specifically, polyester-based carboxylic acids, polyether-based carboxylic acids, polyacrylic-based carboxylic acids, aliphatic-based carboxylic acids, polysiloxane-based carboxylic acids, polyester-based phosphoric acids, polyether-based phosphoric acids, polyacrylic-based phosphoric acids, aliphatic-based phosphoric acids, polysiloxane-based phosphoric acids, polyester-based phenols, polyether-based phenols, polyacrylic-based phenols, polysiloxane-based phenols, etc. One type of dispersant may be used alone, or two or more types may be used in combination.
[0153] Any generally known thermoplastic resin may be used as the thermoplastic resin. Specifically, examples include vinyl polymers such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, (meth)acrylic resin, ethylene-vinyl acetate copolymer, and ethylene-vinyl alcohol copolymer; polyesters such as polylactic acid resin, polyethylene terephthalate, and polybutylene terephthalate; polyamides such as nylon and polyamideamine; polyvinyl acetal resins such as polyvinyl acetoacetal, polyvinyl benzal, and polyvinyl butyral resin; ionomer resin, polyphenylene ether, polyphenylene sulfide, polycarbonate, polyether ether ketone, polyacetal, ABS resin, LCP (liquid crystal polymer), fluoropolymer, urethane resin, silicone resin, and various elastomers. The thermoplastic resin may be a modified product of the resins exemplified above.
[0154] These thermoplastic resins may be uniform within the resin phase of the resin cured product, or their shape may be recognizable through phase separation. In the case of phase separation, the shape of the thermoplastic resin in the resin cured product may be particulate or fibrous. Additionally, the thermoplastic resin may be included as the organic filler described above.
[0155] In some cases, the inclusion of a thermoplastic resin can impart appropriate elongation to the resin composition and relieve stress, thereby suppressing the occurrence of cracks during temperature cycle testing.
[0156] When the thermoplastic resin and the aforementioned organic filler are insoluble in the thermosetting resin, the viscosity of the resin composition is prevented from increasing, and, for example, when molded into a sheet as described below, the smoothness of the sheet surface can be improved. In this case, by simultaneously mixing the thermoplastic resin and the organic filler insoluble in the thermosetting resin with a large amount of inorganic filler, the component phase that exhibits good elongation due to thermoplasticity can be efficiently dispersed within the resin cured product, making it easy to relieve stress. Therefore, the occurrence of cracks in the resin cured product can be suppressed without lowering the elastic modulus of the resin cured product. For this reason, polyamide resins such as nylon and cellulose resins are preferred as the thermoplastic resin, and polyamide resins such as nylon are particularly preferred.
[0157] The resin composition of the present invention may optionally additionally contain an organic solvent to improve applicability when forming a sheet-like resin cured product through a coating process, for example.
[0158] Examples of organic solvents that may be contained in the resin composition of the present invention include methyl ethyl ketone, cyclohexanone, propylene glycol monomethyl ether acetate, butyl acetate, isobutyl acetate, propylene glycol monomethyl ether, etc. One type of organic solvent may be used alone, or two or more types may be used in combination.
[0159] When the resin composition of the present invention optionally contains an organic solvent, the content of the organic solvent is appropriately determined according to the handling properties of the resin composition during the production of the resin cured product, the shape before curing, drying conditions, etc. When the resin composition of the present invention is a slurry provided for the coating process described later, it is preferable to use the organic solvent such that the concentration of the solid content (total of components other than the solvent) in the resin composition of the present invention or the resin composition of the present invention after the addition of the inorganic filler described later is 10 to 90 mass%, particularly 40 to 80 mass%.
[0160] In addition, when the resin composition of the present invention is in the form of a sheet after undergoing processes such as coating and drying, it is preferable to use an organic solvent such that the concentration of solids (total of components other than the solvent) in the resin composition of the present invention or the resin composition of the present invention after adding the inorganic filler described below is 95 mass% or more, and it is more preferable to use it such that it is 98 mass% or more.
[0161] [Preparation of Resin Composition and Cured Resin]
[0162] The resin composition of the present invention and the method for manufacturing the resin cured product of the present invention described above are explained below by way of example by explaining the method for manufacturing a sheet-shaped resin cured product comprising the resin cured product of the present invention.
[0163] A sheet-shaped resin cured product can be manufactured by commonly used methods. For example, it can be obtained by preparing a resin composition of the present invention, molding the resin composition into a sheet, and curing it.
[0164] A resin composition can be obtained by uniformly mixing an inorganic filler, a thermosetting resin, a thermosetting catalyst, and other components added as needed by stirring and kneading.
[0165] For mixing, general mixing devices such as mixers, kneaders, single-screw mixers, and twin-screw mixers can be used, and heating may be performed as needed during mixing.
[0166] The mixing sequence of each component is arbitrary as long as there are no special problems such as reactions or the occurrence of precipitates. For example, a method may be used in which a thermosetting resin component is mixed and dissolved in an organic solvent (e.g., methyl ethyl ketone) to prepare a resin solution, an inorganic filler and other components are sufficiently mixed and added to the obtained resin solution and mixed, and then an additional organic solvent is added and mixed to adjust the viscosity, and then additives such as a curing agent, a curing accelerator, and a dispersant are added and mixed.
[0167] A method for molding and curing the prepared resin composition into a sheet can use a generally used method.
[0168] A method for forming a slurry-type resin composition into a sheet can be obtained by forming the resin composition into a sheet using methods such as the doctor blade method, solvent casting method, or extrusion film formation method.
[0169] The solvent in the resin composition can be removed by known heating methods such as a hot plate, a hot air furnace, an IR heating furnace, a vacuum dryer, or a high-frequency heater.
[0170] Hereinafter, an example of a method for manufacturing a resin cured product using a slurry-type resin composition is described.
[0171] [Coating Process]
[0172] First, a slurry-type resin composition is applied to the surface of a substrate to form a coating film (sheet-type resin composition). Specifically, a coating film is formed on the substrate using a slurry-type resin composition by a dip method, spin coat method, spray coat method, blade method, or any other method. For applying the slurry-type resin composition, a coating device such as a spin coater, slit coater, die coater, or blade coater may be used. By using a coating device, it is possible to uniformly form a coating film of any thickness on the substrate.
[0173] As for the substrate, the copper foil and PET film described below are generally used, but are not particularly limited.
[0174] [Drying Process]
[0175] A coating film formed by applying a slurry-type resin composition is dried at a temperature typically 10 to 150°C, preferably 25 to 120°C, and more preferably 30 to 110°C to remove solvents and low molecular weight components. If the drying temperature is below the upper limit, the curing of the thermosetting resin in the slurry-type resin composition is inhibited, and the resin in the sheet-type resin composition tends to flow during the subsequent pressurization process, making it easier to remove voids. In addition, if the drying temperature is above the lower limit, the solvent can be effectively removed, and productivity tends to improve.
[0176] The drying time is not particularly limited and can be appropriately adjusted depending on the state of the resin composition in the slurry, the drying environment, etc. The drying time is preferably 1 minute or more, more preferably 2 minutes or more, even more preferably 5 minutes or more, even more preferably 10 minutes or more, particularly preferably 20 minutes or more, and most preferably 30 minutes or more. Meanwhile, the drying time is preferably 4 hours or less, and more preferably 2 hours or less.
[0177] If the drying time is greater than or equal to the above lower limit, the solvent can be sufficiently removed, which tends to suppress the formation of residual solvent into voids within the cured resin. If the drying time is less than or equal to the above upper limit, productivity is improved, which tends to suppress manufacturing costs.
[0178] [Pressure Process]
[0179] After the drying process, it is preferable to perform a pressurization process on the obtained sheet-shaped resin composition for purposes such as bonding inorganic fillers together to form a heat path, eliminating voids and pores within the sheet, and improving adhesion to the substrate.
[0180] In the pressurization process, the heating temperature of the sheet-like resin composition on the substrate is not particularly limited. The heating temperature is preferably 10°C or higher, more preferably 20°C or higher, and even more preferably 30°C or higher. The heating temperature is preferably 300°C or lower, and more preferably 250°C or lower. If this heating temperature is within the above numerical range, the melt viscosity of the resin in the coating film can be lowered, thereby eliminating voids and pores within the cured resin. Furthermore, if heated below the above upper limit, there is a tendency to suppress the decomposition of organic components in the sheet-like resin composition and the cured resin, and voids caused by residual solvents.
[0181] The time of the pressurization process is not particularly limited. The time of the pressurization process is preferably 30 seconds or more, more preferably 1 minute or more, even more preferably 3 minutes or more, and particularly preferably 5 minutes or more. In addition, the time of the pressurization process is preferably 1 hour or less, more preferably 30 minutes or less, and even more preferably 20 minutes or less.
[0182] If the pressurization time is below the upper limit mentioned above, the manufacturing time of the resin cured product can be suppressed, which tends to reduce production costs. On the other hand, if it is above the lower limit mentioned above, voids within the resin cured product can be sufficiently removed, which tends to improve heat transfer performance and dielectric strength characteristics.
[0183] [Curing Process]
[0184] The curing process for completely curing the resin composition of the present invention may be carried out under pressure or without pressure. In addition, the pressure process and the curing process may be carried out simultaneously.
[0185] When the pressurization process and the curing process are performed simultaneously, the load is not particularly limited. It is preferable to apply a load of 2 MPa or more to the resin composition in the form of a sheet on the substrate, more preferable to 5 MPa or more, and more preferable to 9 MPa or more. In addition, the load is preferably 2000 MPa or less, and more preferable to 1500 MPa or less. If the load is below the upper limit, a sheet having high thermal conductivity without voids, etc., in the resin cured in the form of a sheet can be obtained without the secondary particles of the inorganic filler being destroyed. In addition, if the load is above the lower limit, the contact between the inorganic fillers improves, making it easier to form a heat conduction path, and thus a resin cured product having high thermal conductivity can be obtained.
[0186] When the pressurization process and the curing process are performed simultaneously, the pressurization time is not particularly limited. In this case, the pressurization time is preferably 30 seconds or more, more preferably 1 minute or more, more preferably 3 minutes or more, and particularly preferably 5 minutes or more. Also, in this case, the pressurization time is preferably 4 hours or less, and more preferably 3 hours or less. If the pressurization time is below the upper limit mentioned above, the manufacturing time of the resin cured sheet can be suppressed, and thus production costs tend to be reduced. On the other hand, if the pressurization time is above the lower limit mentioned above, voids and pores within the resin cured sheet can be sufficiently removed, and thus heat transfer performance and dielectric strength characteristics tend to be improved.
[0187] When the pressurization process and the curing process are performed simultaneously, the heating temperature of the sheet-shaped resin composition on the substrate is not particularly limited. The heating temperature is preferably 10°C or higher, more preferably 20°C or higher, and even more preferably 30°C or higher. In addition, the heating temperature is preferably 300°C or lower, and more preferably 250°C or lower. If the heating temperature is within the above numerical range, the melt viscosity of the resin in the coating film can be lowered, thereby eliminating voids and pores within the cured resin product. Furthermore, if the heating temperature is below the above upper limit, there is a tendency to suppress voids caused by the decomposition of organic components in the sheet-shaped resin composition and the cured resin product, and residual solvents.
[0188] When only the curing process is performed, the heating temperature of the resin composition in the form of a sheet on the substrate is not particularly limited. In this case, the heating temperature is preferably 10°C or higher, more preferably 50°C or higher, and even more preferably 100°C or higher. In this case, the heating temperature is preferably 500°C or lower, more preferably 300°C or lower, and even more preferably 200°C or lower. If the heating temperature is within the above numerical range, the curing reaction of the resin is effectively carried out. Also, if the heating temperature is within the above numerical range, thermal degradation of the resin can be prevented. Furthermore, if the heating temperature is above the above lower limit, the curing reaction of the resin is carried out more effectively.
[0189] The thickness of the resin cured product is not particularly limited, but is preferably 50 μm or more, more preferably 80 μm or more, and even more preferably 100 μm or more. In addition, the thickness of the resin cured product is preferably 400 μm or less, and more preferably 300 μm or less. If the thickness of the resin cured product is greater than or equal to the lower limit above, dielectric breakdown voltage characteristics are obtained, and the dielectric breakdown voltage tends to improve. In addition, if the thickness of the resin cured product is less than or equal to the upper limit above, miniaturization and thinning of the device can be achieved, and the thermal resistance of the obtained resin cured product (heat dissipation sheet) tends to be suppressed.
[0190] <Composite Molded Body>
[0191] The composite molded article of the present invention comprises a resin cured product of the present invention and a metal. For example, a cured product part made of the resin cured product of the present invention and a metal part made of a metal are laminated. The metal part may be formed on only one side of the cured product part made of the resin cured product of the present invention, or it may be formed on two or more sides. For example, the metal part may be formed on only one side of the resin cured product, or it may be formed on both sides. In addition, the metal part may be patterned.
[0192] Such a composite molded article of the present invention can be manufactured by using a metal part as the above-mentioned substrate and forming a resin cured article of the present invention on the substrate according to the above-mentioned method. Alternatively, it can be manufactured by peeling off a sheet-like resin composition or a resin cured article formed on a substrate different from the metal part from the substrate, and then heat-pressing it onto a metal member that becomes the metal part.
[0193] In this case, the sheet-like resin composition or resin cured product of the present invention is formed in the same manner as above, except that it is applied onto a substrate such as PET that may be treated with a release agent, and then peeled off from the substrate, and the sheet-like resin composition or resin cured product is placed on another metal plate or sandwiched between two metal plates and integrated by applying pressure.
[0194] In this case, a metal plate with a thickness of about 10 μm to 10 cm made of copper, aluminum, nickel-plated metal, etc., can be used as the metal plate. In addition, the surface of the metal plate may be physically treated or chemically treated with a surface treatment agent, and it is more preferable that these treatments be performed from the perspective of adhesion between the resin composition and the metal plate.
[0195] <Semiconductor Devices>
[0196] The semiconductor device of the present invention has a composite molded body of the present invention. The composite molded body of the present invention can be used as a semiconductor device. In particular, it can be usefully used in a power semiconductor device capable of high output and high density by operating at a high temperature.
[0197] Examples
[0198] The present invention will be explained in more detail below through examples, but the present invention is not limited to the following examples. The various conditions and evaluation result values in the following examples represent the preferred range of the present invention, just as the preferred range in the embodiments of the present invention is. The preferred range of the present invention can be determined by taking into account the preferred range in the above-described embodiments and the range resulting from the values of the following examples or the combination of values between examples.
[0199] <Ingredients>
[0200] The raw materials used in the examples and comparative examples are as follows.
[0201] (Thermosetting resin)
[0202] · Resin component 1: Difunctional epoxy resin disclosed in Example 1 of Japanese Patent Publication No. 2006-176658
[0203] · Resin Component 2: Bisphenol F type solid epoxy resin manufactured by Mitsubishi Chemical
[0204] Mass average molecular weight equivalent to polystyrene: 60,000
[0205] · Resin Component 3: Bisphenol A type liquid epoxy resin manufactured by Mitsubishi Chemical
[0206] · Resin Component 4: A polyfunctional epoxy resin manufactured by Nagase Chemtex, comprising a structure having four or more glycidyl groups per molecule
[0207] · Resin Component 5: Hydrogenated Bisphenol A type liquid epoxy resin manufactured by Mitsubishi Chemical
[0208] · Resin Component 6: p-aminophenol type liquid epoxy resin manufactured by Mitsubishi Chemical
[0209] · Resin Component 7: Biphenyl-type solid epoxy resin manufactured by Mitsubishi Chemical
[0210] · Resin Component 8: A polyfunctional epoxy resin manufactured by Nagase Chemtex, comprising a structure having three or more glycidyl groups per molecule
[0211] (Cohesive Weapon Filler)
[0212] · Inorganic filler 1: Boron nitride aggregate particles having a card house structure, manufactured in accordance with the method for manufacturing boron nitride aggregate particles disclosed in the embodiment of International Publication No. 2015 / 119198.
[0213] (Other fillers)
[0214] · Inorganic Filler 2: Manufactured by Admatex, spherical alumina particles
[0215] New Mohs Hardness: 9
[0216] Volume average particle size: 6.5 µm
[0217] Thermal conductivity: 20 ∼ 30 W / m·K
[0218] (Hardening agent)
[0219] · Curing agent 1: MEH-8000H manufactured by Meiwa Chemical. MEH-8000H is a phenol resin-based curing agent.
[0220] (Thermosetting catalyst)
[0221] · Thermosetting curing catalyst 1: 2E4MZ-A manufactured by Shikoku Kasei Co.
[0222] 2E4MZ-A corresponds to 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(17')]-ethyl-s-triazine and has both structures derived from imidazole and structures derived from triazine in one molecule.
[0223] Molecular weight of 2E4MZ-A: 247
[0224] Properties of 2E4MZ-A: Solid
[0225] Melting point of 2E4MZ-A: 215–225 ℃
[0226] Solubility of 2E4MZ-A in DMF: 10 mass% or less
[0227] · Thermosetting curing catalyst 2: 2PHZ-PW manufactured by Shikoku Kaseisha.
[0228] 2PHZ-PW is 2-phenyl-4,5-dihydroxymethylimidazole.
[0229] Molecular weight of 2PHZ-PW: 204
[0230] Properties of 2PHZ-PW: Solid
[0231] Melting point of 2PHZ-PW: 230°C or higher (decomposition at 230°C)
[0232] Average particle size of 2PHZ-PW: Approx. 3 µm
[0233] Solubility of 2PHZ-PW in DMF: 10 mass% or less
[0234] · Thermosetting curing catalyst 3: C11Z-CN manufactured by Shikoku Kasei Co.
[0235] C11Z-CN is 1-cyanoethyl-2-undecylimidazole.
[0236] Molecular weight of C11Z-CN: 275
[0237] Properties of C11Z-CN: Solid
[0238] Melting point of C11Z-CN: 47-52 ℃
[0239] Solubility of C11Z-CN in DMF: Greater than 10 mass%
[0240] · Thermosetting Catalyst 4: 2MAOK-PW manufactured by Shikoku Kaseisha
[0241] 2MAOK-PW is a 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct.
[0242] Molecular weight of 2MAOK-PW: 384
[0243] Properties of 2MAOK-PW: Solid
[0244] Melting point of 2MAOK-PW: 260°C or higher (decomposition at 260°C)
[0245] Average particle size of 2MAOK-PW: Approx. 2 µm
[0246] Solubility of 2MAOK-PW in DMF: 10 mass% or less
[0247] <Example 1>
[0248] Using a rotating and orbiting stirring device, a mixture was prepared with resin component 1, resin component 4, resin component 7, curing agent 1, curing catalyst 1, curing catalyst 2, inorganic filler 1, and inorganic filler 2 in the composition as described in Table 1 below. In addition, when preparing the mixture, methyl ethyl ketone and cyclohexanone were used as solvents in amounts of 18.6 mass% each so that the mixture constituted 62.8 mass% (solid content concentration) of the coating slurry.
[0249] The obtained slurry-type resin composition was applied to a PET substrate using the doctor blade method, and after heating and drying at 60°C for 120 minutes, pressure was applied to obtain a sheet-type resin composition with a thickness of 150 μm. The total content of methyl ethyl ketone and cyclohexanone in the sheet-type resin composition was 1 mass% or less.
[0250] (Fabrication of cured resin for measuring thermal conductivity)
[0251] A resin composition in the form of a sheet was sandwiched between PET layers, and pressurized at 120°C and 9 MPa for 20 minutes to obtain a resin cured product for measuring thermal conductivity. In addition, by the same method, four types of resin cured products with different thicknesses were obtained by pressing two, three, and four sheets of the resin composition stacked in a stacked state, respectively. These four types of resin cured products with different thicknesses were used as resin cured products for measuring thermal conductivity.
[0252] (Fabrication of composite molded bodies for non-measurement of peel strength)
[0253] A sheet-shaped resin composition was sandwiched between two copper plates with a thickness of 105 μm, and pressurized at 120°C and 9 MPa for 30 minutes, then the temperature was increased and pressurized at 175°C and 9 MPa for 30 minutes to obtain a composite molded body for measuring peel strength. In order to secure the tensile portion during the peel test, one of the copper plates was made to have a longer dimension in the longitudinal direction than the sheet.
[0254] (Fabrication of composite molded bodies for reflow testing)
[0255] One copper plate each with a thickness of 500 and 2,000 μm, which had been surface-treated 100 times by #120 lines in advance, was placed between a sheet-like resin composition, and pressure was applied at 120°C and 9 MPa for 30 minutes, then the temperature was raised and pressure was applied at 175°C and 9 MPa for 30 minutes to obtain a composite molded body for reflow testing.
[0256] A copper plate of 500 μm was patterned by etching the composite molded body obtained above using a predetermined method. The pattern was formed so that a circular pattern of φ25 mm remained at two points.
[0257] (Measurement of thermal conductivity)
[0258] The thermal resistance of the resin cured materials for measuring thermal conductivity was measured using the "T3ster DynTIM Tester" manufactured by Mentor Graphics. The thermal conductivity was calculated from the relationship between the film thickness of each of the four types of resin cured materials and the measured thermal resistance value. During measurement, the probe size was set to φ12.8 mm, the fixed pressure to 3400 kPa, and the measurement time to 300 sec. To improve the adhesion between the sample and the probe, "OIL COMPOUND (Product Name: G-747)" manufactured by Shin-Etsu Chemical Co., Ltd. was used.
[0259] (Measurement and evaluation of the Peel intensity ratio)
[0260] One side of the composite molded body was fixed to a jig, and a copper plate with a long dimension along the longitudinal axis from the sheet was fixed to the sample and subjected to tension at 50 mm / min in a direction perpendicular to it. Among the data obtained as a result, the peel strength a was calculated by calculating the average load of the stable region. In addition, the same sheet-like molded body was left at room temperature for 1 day before pressurization, and the composite molded body was fabricated and measured in the same manner to calculate the peel strength b, and the peel strength ratio = b / a was calculated. The peel strength was evaluated according to the following criteria.
[0261] A: The peel intensity ratio is 0.9 or higher.
[0262] B: The peel strength ratio is less than 0.9.
[0263] (Evaluation by Reflow Test)
[0264] The composite molded body for the reflow test was stored for 3 days in an environment of 85°C and 85% RH using a constant temperature and humidity chamber SH-221 (manufactured by Espect). Subsequently, within 30 minutes, the temperature was raised from room temperature to 290°C over 12 minutes under a nitrogen atmosphere, maintained at 290°C for 10 minutes, and then cooled to room temperature (hygroscopic reflow test). Afterward, the interface between the copper plate and the resin cured product was observed using an ultrasonic imaging device FineSAT (FS300III) (manufactured by Hitachi Power Solutions). For the measurement, a probe with a frequency of 50 MHz was used, with a gain of 30 dB and a pitch of 0.2 mm, and the sample was placed in water. It was evaluated according to the following criteria.
[0265] A: Interfacial delamination is not observed.
[0266] B: Delamination was observed at the interface.
[0267] <Examples 2, 3, Comparative Examples 1–4>
[0268] After obtaining a sheet-like resin composition in the same manner as in Example 1, except that each component was used to form the composition shown in Table 1, a resin-cured product for measuring thermal conductivity, a composite molded body for measuring peel strength, and a composite molded body for reflow testing were produced and evaluated.
[0269] The results of each example are shown in Table 1.
[0270]
[0271] From the results of the examples, it was shown that the resin composition of the present invention, by containing multiple thermosetting catalysts, results in a resin cured product having high thermal conductivity. Furthermore, it was shown that the storage stability of the resin composition is improved, and the adhesion between the metal and the cured product in the reflow test is also improved.
[0272] Industrial applicability
[0273] According to the resin composition of the present invention, a cured product is obtained that is difficult to peel off at the interface when combined with a metal, as it has excellent thermal conductivity and adhesion to metal.
[0274] The resin cured product of the present invention has excellent thermal conductivity and adhesion to metal, making it difficult to delaminate at the interface when combined with metal.
[0275] The composite molded article of the present invention has excellent thermal conductivity and adhesion between the resin cured product and the metal, making it difficult to delaminate at the interface.
[0276] The semiconductor device of the present invention has excellent heat dissipation performance and adhesion between the resin cured material and the metal, making it difficult to peel off the interface.
Claims
Claim 1 A resin composition comprising an inorganic filler, a thermosetting resin, and a thermosetting catalyst, wherein the inorganic filler comprises an aggregated inorganic filler, the thermosetting resin comprises an epoxy resin, two or more thermosetting catalysts having a melting point of 100°C or higher, and the two or more thermosetting catalysts comprise a polyfunctional epoxy resin having a structure derived from imidazole and having three or more epoxy groups per molecule, in an amount of 5% or more and 50% or less of the total epoxy resin. Claim 2 A resin composition according to claim 1, wherein at least one of the thermosetting catalysts having a structure derived from imidazole additionally has a structure derived from triazine in one molecule. Claim 3 A resin composition according to claim 1, wherein at least one of the thermosetting catalysts has a melting point of 200°C or higher. Claim 4 A resin composition according to claim 1, wherein the resin composition optionally additionally contains a solvent, and the content of the thermosetting catalyst is 0.1 to 10 mass% with respect to 100 mass% of the resin composition excluding the inorganic filler and the optionally included solvent. Claim 5 A resin composition according to claim 1, wherein the solubility of the thermosetting catalyst for N,N-dimethylformamide at 25°C is 10 mass% or less. Claim 6 A resin composition according to claim 1, wherein the agglomerated inorganic filler comprises boron nitride agglomerated particles. Claim 7 A resin composition according to claim 1, further containing alumina. Claim 8 A resin composition according to claim 1, wherein the agglomerated inorganic filler is a boron nitride agglomerated particle having a card house structure. Claim 9 A resin composition according to claim 1, wherein the proportion of epoxy resin in the resin composition excluding inorganic fillers and thermosetting catalysts is 20 mass% or more and 100 mass% or less. Claim 10 A resin cured product using a resin composition described in any one of claims 1 to 9. Claim 11 A composite molded article having a resin cured product described in claim 10 and a metal. Claim 12 A semiconductor device having a composite molded body as described in claim 11. Claim 13 delete Claim 14 delete
Citation Information
Patent Citations
Resin material and laminate
WO2018139645A1
Resin material, method for producing resin material, and laminate
WO2018235918A1
One part thermosetting resin composition, method for producing electronic part using the same, and electronic part
JP2012067274A
Heat release insulation sheet, and laminate structure having sheet cured article as insulation layer
JP2019119883A